2000
DOI: 10.1152/ajpendo.2000.279.5.e1045
|View full text |Cite
|
Sign up to set email alerts
|

Retinoic acid and host-pathogen interactions: effects on inducible nitric oxide synthase in vivo

Abstract: Vitamin A and its metabolite retinoic acid modulate the host response to pathogens through poorly characterized mechanisms. In vitro studies have suggested that retinoic acid decreases inducible NO synthase (NOS2, or iNOS) expression, a component of innate immunity, in several cell types stimulated with lipopolysaccharide (LPS) or cytokines. This study investigated the effect of retinoic acid on LPS-stimulated NOS2 expression in vivo. Wistar-Kyoto rats received all-trans retinoic acid (RA, 10 mg/kg) or vehicle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 43 publications
2
25
0
1
Order By: Relevance
“…RA (Roche, Kaiseraugst, Switzerland) was dissolved in the vehicle (liquid paraffin) at a final concentration of 10 mg/ml. RA-supplemented (RA-S) mice received daily intraperitoneal injections of RA (10 mg/kg body weight) for 5 consecutive days in a manner similar to that previously described (37). Control mice received an equal volume of the vehicle.…”
Section: Methodsmentioning
confidence: 99%
“…RA (Roche, Kaiseraugst, Switzerland) was dissolved in the vehicle (liquid paraffin) at a final concentration of 10 mg/ml. RA-supplemented (RA-S) mice received daily intraperitoneal injections of RA (10 mg/kg body weight) for 5 consecutive days in a manner similar to that previously described (37). Control mice received an equal volume of the vehicle.…”
Section: Methodsmentioning
confidence: 99%
“…A low dose LPS-mediated activation of the NOS2 pathway (18,19) was obtained by i.p. injection of LPS (6 mg/kg body weight (bw)) to all rats, except those of the control group (n ϭ 4) that received 500 l of 0.9% NaCl i.p.…”
Section: Experimental Protocolsmentioning
confidence: 99%
“…Under these circumstances, NOS2 inhibitors might have beneficial effects on host survival (typically high LPS doses in rodent models; Ref. 18). Other types of stimuli, such as the low dose LPS used in the present study, result in NOS2 induction and low level/absent COX-2 induction with NO or ONOO Ϫ , resulting in increased COX-1-derived end products.…”
Section: Beneficial and Deleterious Effects Of Nos2 Inhibitorsmentioning
confidence: 99%
“…31 Moreover, sentrin/SUMO-specific protease1 (SENP1) plays a key role in the regulation of HIF1α stability. 32 Although the effects of ATRA on the production of nitric oxide, a donor for nitrosylation, are controversial, 33,34 we still investigated whether the S-nitrosylation or deSUMOylation of HIF-1α protein contributes to the ATRA-induced increase of HIF-1α protein. We found that L-NAME and 1400W, potent inhibitors of nitric oxide synthases, 31 failed to inhibit the ATRA-induced increase of HIF-1α protein in complete culture medium, while SENP1 expression was slightly upregulated during ATRA treatment (data not shown).…”
mentioning
confidence: 99%